Regulation, Competition and Productivity Convergence - Conway, Paul (OECD Publishing, 2006)
This paper investigates the effect of product market regulations on the international diffusion of productivity shocks. The empirical results indicate that restrictive product market regulations slow the process of adjustment through which best practice production techniques diffuse across borders and new technologies are incorporated into the production process. This suggest that remaining cross-country differences in product market regulation can partially explain the recent observed divergence of productivity in OECD countries, given the emergence of new general-purpose technologies over the 1990s. The paper also investigates two channels through which product market regulations might affect the international diffusion of productivity shocks, namely the adoption of information and communications technology and the location decisions of multi-national enterprises. In both cases the effect of anticompetitive product market regulation is found to be negative and significant
Keywords: Economics